Monthly Chaetocerotales diversity and abundance, and its relationship with water physicochemical parameters and phytoplankton diversity in Carey Island mangrove ecosystem, Malaysia - NURUL SHAHIDA REDZUAN; pozi milow (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Redzuan NS, Milow P. 2021. Monthly Chaetocerotales diversity and abundance, and its relationship with water physicochemical parameters and phytoplankton diversity in Carey Island mangrove ecosystem, Malaysia. Biodiversitas 22: 2919-2927. Globally, phytoplankton of order Chaetocerotales has been reported to cause monospecific bloom events. The blooms that normally lead to ecosystem instability, also physically responsible for histological and physical damages to fishes. Regarding that order Chaetocerotales often display significant temporal variability, this study aimed to investigate the monthly variability of species composition and cell density of phytoplankton of order Chaetocerotales during high tide period immersion were investigated over a year period. In addition, this present study also aimed to analyze the relationship between Chaetocerotales diversity and abundance with physical and chemical parameters that potentially controlling their temporal variability. Samplings were carried out from April 2009 until March 2010 in the mangrove ecosystem of Carey Island, Selangor, Malaysia. Of 84 phytoplankton taxa recorded, 18 species belonged to order Chaetocerotales, i.e. the genera Bacteriastrum and Chaetoceros. Although initially the sampling was designed to study the overall phytoplankton, the study also aimed at high temporal variability in Chaetocerotaceae cells density has called for this paper to be written. Interestingly, order Chaetocerotales showed to have negative correlation with the total phytoplankton species. Chaetocerotales blooms at the study site were represented by multispecies blooms, with Chaetoceros curvisetus as the highest species in the events. Dissolved oxygen, on the other hand, showed to have negative correlation Chaetocerotales' cells density. All of the species, except the Chaetoceros subtilis and Chaetoceros neglectus displayed significant temporal monthly variability across twelve months of sampling. Nitrate, phosphate and temperature are potentially the parameters that stimulate the growth of the order, consequently causing bloom events.